Post-COVID-19 pandemic: Standard operating procedures for gross anatomy laboratory in the new standard - Onigbinde, O.A. (Morphologie, 2021)
The culture of cadaver dissection remains the most commonly used method of practical teaching and learning of human anatomy. Anatomist and medical professionals considered cadaver dissection as the gold standard for teaching and learning anatomy in detail. The increase seen in the establishment of new medical training institutions globally has consequently led to a proportionate increase in the sourcing for cadavers. Moreover, the surge in mortality rates following the recent coronavirus disease 2019 (COVID-19) pandemic with no cure or approved vaccine has been a source of concern for academia, especially on the safety in the usage of cadavers for dissection. Notwithstanding, several countries continue to depend on unclaimed bodies as the primary source for cadavers, regardless of the cause of death. Besides, body donation is also usually reported to be strained during disease outbreaks thereby putting countries that depend solely on it in a dilemma. This study highlighted the recommended standard operating procedures (SOPs) to be imbibed in gross anatomy dissection halls during and post-COVID-19 pandemic.